SEMUA SUBGRUP SIKLIK DARI GRUP (Zn,+) - Indra Bayu Muktyas; Samsul Arifin (Teorema: Teori dan Riset Matematika, 2018)
Zn adalah is a group under addition modulo n. Cyclic subgroup is subgroup that generated by one of in a group. In group , all cyclic subgroup can be generated by a generator that is the factors of n. in this paper, we will determine all cyclic subgroup of group  using Python.  Key words: group , cyclic subgroup, Python